2009
DOI: 10.1021/jp903792d
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Structural Study of Diphenylpyridine Isomers

Abstract: The energetic and structural study of three diphenylpyridine isomers is presented in detail. The three isomers, 2,6-, 2,5-, and 3,5-diphenylpyridines, were synthesized via Suzuki-Miyaura methodology based on palladium catalysis, and the crystal structures of the isomers were obtained by X-ray diffraction. The relative energetic stabilities in the condensed and gaseous phases as well as volatilities and structures of the three studied isomers were evaluated, regarding the position of the phenyl groups relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Panzella et al (2005) reported that the reaction of either 3-nitrotyrosine or phenylalanine with hypochlorous acid led to the formation of 3,5-diphenylpyridine arising from a Chichibabin-like pyridine synthesis via N-chloroimine intermediates. The isomers, 2,6-DPhPy and 3,5-DPhPy could be synthesized via the SuzukiMiyaura method based on palladium catalysis (Rocha et al, 2009), with the production of halogenated organic compounds. In our study, phenylacetaldehyde and halogenated organic compounds like chloromethyl benzene, and chlorophenylacetaldimine were identified by GC-MS or HPLC-MS, therefore, the presence of the isomer of 2,6-diphenylpyridine was assumed to be related to the above products.…”
Section: Formation Of Disinfection Byproducts Of Phenylalanine Chlorimentioning
confidence: 99%
“…Panzella et al (2005) reported that the reaction of either 3-nitrotyrosine or phenylalanine with hypochlorous acid led to the formation of 3,5-diphenylpyridine arising from a Chichibabin-like pyridine synthesis via N-chloroimine intermediates. The isomers, 2,6-DPhPy and 3,5-DPhPy could be synthesized via the SuzukiMiyaura method based on palladium catalysis (Rocha et al, 2009), with the production of halogenated organic compounds. In our study, phenylacetaldehyde and halogenated organic compounds like chloromethyl benzene, and chlorophenylacetaldimine were identified by GC-MS or HPLC-MS, therefore, the presence of the isomer of 2,6-diphenylpyridine was assumed to be related to the above products.…”
Section: Formation Of Disinfection Byproducts Of Phenylalanine Chlorimentioning
confidence: 99%
“…1.1.1 ) 7 . The crystal analysis reveals the following; (i) both the pyrrole units are amine type (N1‐H1′ and N3‐H3′), such exclusive presence of dipyrromethane unit in macrocylic core is hitherto unknown in the calixphyrin chemistry; (ii) one of the pyrrole unit (N1) is highly tilted by 68.84(5)° as compared to other pyrrole (N3) 30.78(5)° and pyridine units ( Py ) by 55.91(4)° and these units were deviated from the mean macrocyclic plane containing 16 inner core atoms; (iii) overall the macrocycle exhibits partial ruffled conformation to mitigate the steric repulsion caused by the contracted core and (iv) as compared to 3,5‐diphenylpyridyl unit, [17] the inverted pyridine ring is almost perpendicular to the fused‐phenyl units with the dihedral angle of 85.09(5)° ( o1 ) and 66.67(6)° ( o2 ), respectively. Furthermore, the carbon–carbon bond lengths of pyridine( Py ) unit in 7 are between 1.396(2) Å and 1.336(2) Å, pyrrole rings (N1 & N3) are from 1.425(2) Å to 1.357(2) Å and phenyl rings ( o1 & o2 ) are between 1.401(2) Å and 1.370(2) Å (Figure S23) confirms that each heterocyclic rings maintain its individual aromatic character.…”
Section: Figurementioning
confidence: 97%